The Relationship Between Santri's Knowledge About Scabies And Personal Hygiene With The Incidence Of Scabies In Pesantren Azzainiyyah Sukabumi - Mawarni, Jesica Restu; Hadiyanto , Hendri; Lutiyah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Scabies is a contagious skin disease caused by Sarcoptes scabiei mites that infest a person. The disease often occurs in places with high density and poor sanitation, such as in boarding schools. Poor knowledge about hygiene, poor hygiene care, and unfavorable environmental conditions, such as lack of access to sanitation, are the main risk factors for scabies. The purpose of this study was to see how santri's knowledge of scabies, personal hygiene care, and scabies cases in Pesantren Azzainiyyah Sukabumi correlate with each other. This study utilized a descriptive correlative design and cross-sectional technique. The systematic method of random sampling consisted of 62 students. Data were collected through questionnaires containing variables of knowledge about scabies, personal sanitation, and scabies cases. Chi-Square test was used to analyze univariate and bivariate data. The result of P value obtained from chi Square test for asymp sig. (2-sided) is 0.000. This value shows the result of p,0.05 and means that Ha is accepted and Ho is rejected. So it can be concluded that there is a significant relationship between the relationship between santri knowledge about scabies and personal hygiene with the incidence of scabies. It can be concluded that there is a significant correlation between the level of knowledge of students about scabies and personal hygiene habits with the number of scabies cases that occur in Pesantren Azzainiyyah Sukabumi. Lack of knowledge and poor personal hygiene habits increase the likelihood of getting scabies. It is recommended for pesantren managers to provide regular health education on the importance of personal hygiene and scabies prevention.